IMPLEMENTASI PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDes) TAHUN 2021 DI DESA KOJA DOI KECAMATAN ALOK TIMUR KABUPATEN SIKKA - Nasrullah; Abdul Kholiq; Nurdin H Abd Rahman S. (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
The research aims to describe: 1) The implementation of community empowerment through the development of a Tourism Village in Koja Doi Village, East Alok District, Sikka Regency, 2) The form of community empowerment through the development of a Tourism Village in Koja Doi Village, East Alok District, Sikka Regency, 3) The results of community empowerment in Koja Doi through the development of Tourism Villages in Koja Doi Village, East Alok District, Sikka Regency. This research is a qualitative research. The subjects of this study were the Koja Doi Village Government, the Tourism Awareness Group, and the Koja Doi Village community. Data collection techniques were carried out through interviews, observation and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the study revealed that 1) Community empowerment through the development of Tourism Villages was carried out through three stages, namely the awareness stage, the ability transformation stage and the intellectual ability improvement stage. 2) The form of community empowerment through the development of Tourism Villages has involved many local communities in improving community skills and independence, including tourism awareness counseling, tourism village management training, SOP training, scouting, entrepreneurship, catering service training. 3) The results of community empowerment through the development of the Koja Doi Tourism Village in the Koja Doi Village are increasing community skills and independence, developing the management of the Koja Doi Tourism Village, and maximizing natural and cultural resources. The increase in community skills and independence can be seen from the formation of tourism catering work groups, and guide groups from the community who have attended various kinds of training so that they acquire and improve skills and additional income.